Educational research and innovation the nature of problem solving using research to inspire 21st century learning (OECD Publishing, 2017)
- Foreword and Acknowledgements - Executive summary - The development and assessment of problem solving in 21st-century schools - Analytical problem solving: Potentials and manifestations - Problem solving: Understanding complexity as uncertainty - Problem solving from a mathematical standpoint - The PISA 2012 assessment of problem solving - Interactive problem solving: Exploring the potential of minimal complex systems - The history of complex problem solving - Empirical study of computer-based assessment of domain-general complex problem-solving skills - Factors that influence the difficulty of problem-solving items - Assessing complex problem solving in the classroom: Meeting challenges and opportunities - Log-file data as indicators for problem-solving processes - Educational process mining: New possibilities for understanding students' problem-solving skills - EcoSphere: A new paradigm for problem solving in complex systems - Assessment of collaborative problem-solving processes - Assessing conversation quality, reasoning, and problem solving with computer agents - Epilogue.
Description based on publisher supplied metadata and other sources